Pembuatan ice breaking dengan pendekatan kearifan lokal Sasak dalam layanan bimbingan klasikal - Marfuatun Marfuatun; Siti Sarah; Nusuki Nusuki; Yosi nur kholisho (Educatio, 2022)
Counseling service often used in schools provides classical guidance services, but this service often causes boredom. So that a counselor is often given a refresher by giving an ice-breaking. Ice-breaking forms are very diverse, ranging from average body stretching to games. The existence of local games needs to be appointed as an ice breaker to introduce children who currently do not know many traditional games around them. However, the teacher's lack of creativity makes the variety of ice breakers used in service delivery, especially ice breaking, based on local wisdom. That an ice-breaking guide was made as a teacher guide, so the purpose of this study was to develop a media for guidance and counseling services in the form of an ice-breaking guide book with a practical and effective local wisdom approach used when carrying out services for students. The method used in this study is Research and Development (RD) concerning the ADDIE development model (Analysis, design, development, implementation, evaluation). Based on the results of the feasibility test of media experts on the ice breaking guide book with the local wisdom approach, it can be seen that the ice breaking guide book product with the Lombok local wisdom approach can be categorized as "Eligible" 33.96 X 41.88 with a total score of 37, while the results of the feasibility test material experts are in the "Very Eligible" category (X 41.88). The results of user responses get a percentage of 80%, which is in the high category so that it can be concluded that the ice breaking guide book with an approach to local knowledge of the Lombok area.